Complete denture replacement: a 20-year retrospective study of adults receiving publicly funded dental care - Taylor Marietta; Masood Mohd; Mnatzaganian George (JAPAN PROSTHODONTIC SOC, 2022)
Purpose: There is little evidence as to what is the appropriate replacement interval for complete dentures. The aim of this study was to determine the longevity of complete dentures in a population of publicly insured adults across a 20 year observation period.
Methods: The records of 187,227 Australian adults who accessed complete denture treatment through public clinics between 2000-2019 were assessed. Time to denture replacement was modelled using a Weibull regression and a competing risk regression to adjust for the competing risk of mortality.
Results: Over a 20-year period, 27.7% of dentures were replaced, with a mean longevity of 6.06 (SD: 3.93) years. Pairs of complete dentures had greater mean longevity than single dentures (p<0.001). Approximately 4.6% of dentures provided were replaced within 2 years; 18.4% were replaced between 2 and 10 years and 4.6% of replacements occurred after 10 years. Over 70% of adults who received a complete denture did not replace it during the observation period. Dentures provided by denturists had higher levels of replacement than those made by dentists. Participants over 80 years of age had lower rates of denture replacement. Low socio- economic status and living outside a major city were associated with reduced rates of replacement for dentures under 10 years of age.
Conclusion: Complete dentures were commonly replaced after 6 years of service. Pairs of dentures lasted longer than single dentures.